Decoding the nesting fidelity of Olive ridley sea turtles along Odisha coast: A multi-dimensional approach - Rabindra Kumar Sahoo; Subhajit Barik; C. Muthukumar; Meera Swain; Sanjukta Rani Padhi; Balaram Mahanty; Samiran Mandal; Mukunda Keshari Khadanga; Subhasis Pradhan; Pratap Kumar Mohanty; Uma Sankar Panda (Ocean & Coastal Management, 2026)

Salinity and nutrient driven shifts in diatom dominance along the Tamil Nadu coast during the northeast monsoon - M.D. Bharathi; C. Muthukumar; B. Charan Kumar; Deviram Garlapati; Sivaji Patra; K. Ramu; M.V. Ramana Murthy; R.S. Kankara (Marine Pollution Bulletin, 2026)

Prevalence of emerging contaminants in the outlet of sewage treatment plants: an evidential report from Kerala, India with future concerns - Kochuparambil Ajayaghosh Akhilghosh; Athira Ramesh; Vijayalekshmi Padmachandran Aiswriya; Salman Farissi; P. S. Nishmitha; C. T. Aravindakumar; M. Thalamadai Karuppiah; Muthukumar Muthuchamy; Anbazhagi Muthukumar (Environmental Sustainability, 2026)

A critical review on technical advances and multifaceted role of carotenoids in human health with special emphasis on metabolic diseases - Sayani Roy; K. C. Dora; Siddhnath Kumar; Pooja Saklani; A. Muthukumar; Fatih Ozogul; K. C. Harisankar; R. D. Mutum; S. Celine Hilda Mary; V. K. R. Surasani; P. K. Dara (Phytochemistry Reviews, 2026)

Biosensing and Biotechnological Applications of Nanofillers: Current Status and Perspectives - Muthukumar Raghunathan; Ashish Kapoor; Praveen Kumar; S. C. Tripathi; Shafiul Haque; Dan Bahadur Pal (Indian Journal of Microbiology, 2025)

Molecularly Imprinted Polymers Coupled with Cellulosic Paper-Based Analytical Devices for Biosensing Applications - Ashish Kapoor; Muthukumar Raghunathan; Praveen Kumar; S. C. Tripathi; Shafiul Haque; Dan Bahadur Pal (Indian Journal of Microbiology, 2025)

Recurrent Swarms of Planktonic Shrimp Luciferidae De Haan, 1849 (Order: Decapoda) in the Neritic Waters of Tamil Nadu, Southeast Coast of India - R. S. Sathishkumar; B. Charan Kumar; C. Muthukumar; N. Logesh; Sanitha K. Sivadas; K. Ramu; M. V. Ramana Murthy (Marine Ecology, 2024)
Luciferidae (Decapoda) are an important component of mesozooplankton in pelagic food webs. This study investigated the spatiotemporal distribution and frequency of Luciferidae swarms along the Tamil Nadu coast, as observed during coastal monitoring cruises conducted between 2019 and 2022. Data were collected on various hydrobiological factors, including surface water temperature, salinity, chlorophyll a , zooplankton biomass, and the abundance of other mesozooplankton (such as copepods, cladocerans, and others) across eight locations in the coastal waters of Tamil Nadu, India. Salinity values were generally low ( Belzebub hanseni Nobili, 1905, as the only organism responsible for swarm formation, with its occurrence peaking in January 2022. During this period, B. hanseni reached a maximum abundance of 3294 ind. m −3 for adults and 4056 ind. m −3 for larvae, together contributing approximately 27% of the total zooplankton abundance. Swarms of B. hanseni were observed a total of seven times over the course of the study, correlating with periods of low sea surface temperature and high food availability. Pearson's correlation analysis revealed a significant relationship between the abundance of copepods and B. hanseni ( r = 0.84; p B. hanseni in the nearshore waters of the Tamil Nadu coast is largely driven by food availability and optimal environmental conditions, including water temperature and monsoonal influences. The findings also suggest that geographical features, such as mangrove habitats, may contribute to the occurrence of B. hanseni swarms in this region.

Identification of groundwater potential zones of Alappuzha (Kerala) in South India integrating AHP and GIS - Selvam Sekar; Akhila V. Nath; Priyadarsi Debajyoti Roy; Sang Yong Chung; Hussam Eldin Elzain; Paula C. S. Carvalho; Muthukumar Perumal (Environment, Development and Sustainability, 2024)

The impact of addition of pearl millet starch-germ complex in white bread on nutritional, textural, structural, and glycaemic response: Single blinded randomized controlled trial in healthy and pre-diabetic participants - R. Vidhyalakshmi; Pichan Prabhasankar; S.P. Muthukumar; C. Prathima; M.S. Meera (Food Research International, 2024)

First report on the occurrence of Gonyaulax polygramma bloom during the onset of Noctiluca scintillans bloom along the Tuticorin coast, southeast coast of India - M.D. Bharathi; C. Muthukumar; R.S. Sathishkumar; K. Ramu; M.V. Ramana Murthy (Marine Pollution Bulletin, 2023)

Assessment of phytoplankton diversity, distribution, and environmental variables along the southeast coast of India - P. Sathish Kumar; G. Dharani; J. Santhanakumar; Dilip Kumar Jha; Vikas Pandey; S. Venkatnarayanan; J. Prince Prakash Jebakumar; C. Muthukumar; R. Arthur James (Frontiers in Marine Science, 2023)
Coastal waters are dynamic because of anthropogenic activities that contribute nutrients and contaminants. These changes have the potential to alter patterns of primary production and thus pelagic food webs. Here, we investigated the spatial variation of the phytoplankton community and its response to changing environmental variables at 84 stations along the five coastal districts of Tamil Nadu (TN). During the present study, 85 phytoplankton species were recorded, such as diatoms (64), dinoflagellates (18), silicoflagellates (1), and Cyanophyceae (2). The maximum phytoplankton abundance was recorded on the Thanjavur coast and gradually decreased towards the south coast of Tamil Nadu. Among the phytoplankton community, 50% was dominated by pennate diatoms, attributed to higher NO 3 − concentrations in the coastal waters due to agricultural discharge. Cluster analysis revealed that Ramanathapuram and Tirunelveli formed a closed cluster, whereas Thanjavur and Pudukottai formed a separate closed cluster associated with higher nutrient and metal concentrations, highlighting the difference in physicochemical parameters between the northern and southern districts of the TN coast. Relatively high nutrient concentrations in the coastal waters of northern districts are of greater concern, which could impact the coastal ecosystem. Coastal eutrophication is becoming a widespread phenomenon, causing disruption in the food chain and ecosystem balances and hence requiring regular monitoring and management.

RETRACTED: Pore size variation of nano-porous material fixer on the engine bowl and its combined effects on hybrid nano-fuelled CI engine characteristics - T. Sathish; Ümit Ağbulut; K. Muthukumar; R. Saravanan; Mamdooh Alwetaishi; Saboor Shaik; C. Ahamed Saleel (Fuel, 2023)

An absorber of parabolic trough collector for hydrogen production in a solid oxide fuel cell - T. Sathish; C. Sailaja; R. Saravanan; Pelluru Suresh; M. Anish; M. Rajasimman; Usha Sambath; N. Sabarirajan; K. Muthukumar; Sang-Woo Joo; Yasser Vasseghian (Fuel, 2023)

Pesticide analytical screening system (PASS): A novel electrochemical system for multiplex screening of glyphosate and chlorpyrifos in high-fat and low-fat food matrices - Durgasha C. Poudyal; Vikram Narayanan Dhamu; Manish Samson; Sriram Muthukumar; Shalini Prasad (Food Chemistry, 2023)

Experimental challenge of the freshwater fish pathogen Aeromonas hydrophila Ah17 and its effect on snakehead murrel Channa striata - Samayanpaulraj Vignesh; Govindaraj Krishnaveni; J. C. Walter Devaa; Sivaramapillai Muthukumar; Ramesh Uthandakalaipandian (Aquaculture International, 2022)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Physiological and transcriptional responses of Baccharis halimifolia to the explosive “composition B” (RDX/TNT) in amended soil - Asjad Ali; Julie C. Zinnert; Balasubramaniam Muthukumar; Yanhui Peng; Sang-Min Chung; C. Neal Stewart (Environmental Science and Pollution Research, 2014)

Introgression of bacterial leaf blight resistance and aroma genes using functional marker-assisted selection in rice (Oryza sativa L.) - R. K. Salgotra; B. B. Gupta; Reginald J. Millwood; Muthukumar Balasubramaniam; C. N. Stewart (Euphytica, 2012)

Optimization of Antimicrobial Production by a Marine Actinomycete Streptomyces afghaniensis VPTS3-1 Isolated from Palk Strait, East Coast of India - R. Vijayakumar; K. Panneerselvam; C. Muthukumar; N. Thajuddin; A. Panneerselvam; R. Saravanamuthu (Indian Journal of Microbiology, 2012)

Occurrence of alfalfa (Medicago sativa L.) populations along roadsides in southern Manitoba, Canada and their potential role in intraspecific gene flow - Muthukumar V. Bagavathiannan; Robert H. Gulden; Rene C. Van Acker (Transgenic Research, 2011)

The demography of feral alfalfa (Medicago sativa L.) populations occurring in roadside habitats in Southern Manitoba, Canada: implications for novel trait confinement - Muthukumar V. Bagavathiannan; Robert H. Gulden; Graham S. Begg; Rene C. Van Acker (Environmental Science and Pollution Research, 2010)